2020
DOI: 10.7717/peerj.9159
|View full text |Cite
|
Sign up to set email alerts
|

GISA: using Gauss Integrals to identify rare conformations in protein structures

Abstract: The native structure of a protein is important for its function, and therefore methods for exploring protein structures have attracted much research. However, rather few methods are sensitive to topologic-geometric features, the examples being knots, slipknots, lassos, links, and pokes, and with each method aimed only for a specific set of such configurations. We here propose a general method which transforms a structure into a ”fingerprint of topological-geometric values” consisting in a series of real-valued… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The user may analyze either two parts of the same chain (specified by the indices) or two separate chains. The GLN was already used to study the conformation and entanglement of proteins [ 7 , 8 , 13 , 27 , 46 , 47 ] and chromosomes [ 60 ].…”
Section: Topoly Featuresmentioning
confidence: 99%
“…The user may analyze either two parts of the same chain (specified by the indices) or two separate chains. The GLN was already used to study the conformation and entanglement of proteins [ 7 , 8 , 13 , 27 , 46 , 47 ] and chromosomes [ 60 ].…”
Section: Topoly Featuresmentioning
confidence: 99%
“…The measures introduced in [54,55] were recently developed further in [58] where the Gaussian-integral approach was applied to subsets (fragments) of the protein, via a fingerprinting technique, using the entanglement of sub chains to identify rare conformations in proteins, essentially pairs of subsections of protein which are mutually entangled in some manner which is relatively rare. By contrast, in our case we aim to demonstrate there are tertiary structure motifs which are both common and similar across proteins, but which are not classed as similar in the standard classifications.…”
Section: The Writhe and Its Use Characterising Proteinsmentioning
confidence: 99%
“…In [31] a more rapid metric was created from the same Gaussian integrals as in the other two studies, once again shown to compare favourably to the SCOP benchmark set. The measures introduced in [29] were recently developed further in [32] where the Gaussian-integral approach was applied to subsections (fragments) of the protein, via a fingerprinting technique, using the entanglement of sub-chains to identify rare conformations in proteins. We highlight two aspects of these works that motivate developing our own approach.…”
Section: Plos Computational Biologymentioning
confidence: 99%